2013
DOI: 10.7314/apjcp.2013.14.4.2213
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Mechanism and Possibility of Nano-Suspension Formulation for a Marine Algae Product Fucoxanthin

Abstract: Marine algae contain a wide variety of bioactive compounds; many of them have commercial applications in pharmaceutical, medical, cosmetic, nutraceutical, food and agricultural industries. Natural antioxidants, found in many algae play an important role against various diseases through protection of cells from oxidative AbstractRecently, use of natural products available from marine sources, and especially algae products, are receiving more attention. Scientific evidence for claimed nutraceutical and therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…The main characteristic of an antioxidant is its ability to induce enzymes that trap free radicals (72). Although the biochemical process by which chemoprotective agents protect against cancers that are caused by oxidative stress has not been fully discovered, phase II detoxifying/antioxidant enzymes clearly play a role in fighting oxidative stress and preventing cancers (30).…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristic of an antioxidant is its ability to induce enzymes that trap free radicals (72). Although the biochemical process by which chemoprotective agents protect against cancers that are caused by oxidative stress has not been fully discovered, phase II detoxifying/antioxidant enzymes clearly play a role in fighting oxidative stress and preventing cancers (30).…”
Section: Discussionmentioning
confidence: 99%
“…Fucoxanthin therefore has considerable potential as a nutraceutical ingredient that could be incorporated into functional food and beverage products. However, as with other carotenoids, there are a number of challenges that limit its potential application in foods, such as its low water-solubility, high melting point, and chemical instability (Hii, Choong, Woo, & Wong, 2010;Muthuirulappan & Francis, 2013). Food grade nanoemulsions, which consist of small lipid droplets (<100 nm) dispersed in water, may be a suitable strategy for incorporating carotenoids into foods and of enhancing their bioactivity profiles (McClements, 2011;.…”
Section: Introductionmentioning
confidence: 98%
“…It was also reported that herbal medicine was effective as potential therapy for fatty liver disease, diabetes, and metabolic syndrome [15]. Marine algae have also been shown to possess various biological activities such as antiasthmatic, antidiabetic, anticancer, and antioxidant effects [16,17,18]. However, insect-based bioactive products have rarely been studied, owing to a lack of scientific evidence regarding the safety and beneficial effects of insects despite their wide use as traditional foods or medicines in many countries.…”
Section: Introductionmentioning
confidence: 99%